Measuring the Relationship Maintenance Strategies through PT Pertamina (Persero) Website: www.pertamina.com - Marsefio Sevyone Luhukay (Jurnal InterAct, 2015)
Internet, as a two way communications media provides an interactive and easier way for Public Relations to reach their public. Starting from the internet, e-mail, website, blog, were created, and so did the social media such as Facebook, Twitter, Path, Instagram. Social media helps people to create, share, and publish various contents through online media. Social media also provides people to communicate in two way, maintaining their relationships. To maintain the relationships with the public, Public Relations needs to create a certain way of communicating that will show their good intent. Linda Hon and James Grunig (1999), created a theory about relationship maintenance strategies for Public Relations in order to create and maintain the relationship well. We could see the relationships between Public Relations and their public through the website. This research explains the website contains of PT Pertamina (Persero), The Best BUMN Website of 2014. To be specific, this research’s main topic is “Measuring the Relationship Maintenance Strategies through PT Pertamina (Persero) Website”. This Research using quantitative content analysis method with the Holsti Formula. The results were measured by the indicators as following: (1) Access, (2) Positivity, (3) Openness, (4) Assurances, (5) Networking, (6) Sharing of Task. Those six indicators used to help Public Relations shows the corporate consistency in maintaining relationships with its differences publics through the internet including the corporate website.